Archaeology at ANZAAS, Canberra : a collection of papers presented to Section 25A of the 54th Congress of the Australian and New Zealand Association for the Advancement of Science in May 1984 - Ward, Graeme, 1943-; Canberra Archaeological Society; ANZAAS. Congress 1984 : Australian National University). Section 25A (Archaeology) (Canberra : Canberra Archaeological Society, 1986)
Papers by A.M.C. Murphy and W.B. Wood, L.C. Richards, E. Gott, S.J. Hallam, M-J, Mountain, L.M. Groube, P. Hiscock, R.L.K. Fullagar, I. McBryde, W. Cook and G.S. Morris, P.J.F. Coutts, D. Frankel and D. Gaughwin, D. Morrissey, S.M. Sullivan and R.V.S. Wright separately annotated.
Available from The Secretary, Canberra Archaeological Society, c/- Dept. of Prehistory and Anthropology, Faculty of Arts, Australian National University, GPO Box 4, Canberra, A.C.T. 2601.
Includes bibliographies and index.
Keywords: Archaeology -- Congresses; Archaeology -- Methodology -- Congresses; Archaeological dating -- Congresses; Australia; New Zealand (NZ)